2016
DOI: 10.1007/s13277-016-5157-0
|View full text |Cite
|
Sign up to set email alerts
|

CYLD downregulates Livin and synergistically improves gemcitabine chemosensitivity and decreases migratory/invasive potential in bladder cancer: the effect is autophagy-associated

Abstract: Although GC (gemcitabine and cisplatin) chemotherapy remains an effective method for treating bladder cancer (BCa), chemoresistance is a major obstacle in chemotherapy. In this study, we determined whether gemcitabine resistance correlates with migratory/invasive potential in BCa and whether this relationship is regulated by the cylindromatosis (CYLD)-Livin module. First, we independently investigated the correlation of CYLD/Livin and gemcitabine resistance with the potential for tumor migration and invasivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Therefore, in the present study, we investigated the role of Livin in determining susceptibility to commonly used chemotherapeutic drugs, such as docetaxel, cisplatin and 5-FU, in human HNSCC cell lines. Although several studies have described that Livin contribute to the resistance of various chemotherapeutic drugs including cisplatin in various cancers (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), the present study is the first to demonstrate the correlation between Livin and chemoresistance in human HNSCC.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Therefore, in the present study, we investigated the role of Livin in determining susceptibility to commonly used chemotherapeutic drugs, such as docetaxel, cisplatin and 5-FU, in human HNSCC cell lines. Although several studies have described that Livin contribute to the resistance of various chemotherapeutic drugs including cisplatin in various cancers (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), the present study is the first to demonstrate the correlation between Livin and chemoresistance in human HNSCC.…”
Section: Introductionmentioning
confidence: 53%
“…Livin, a recently discovered IAP, is composed of a single BIR domain and a RING motif (9). Livin has been implicated in chemoresistance in various cancers (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). It has been reported to play a role in resistance to cisplatin in bladder cancer, renal carcinoma, gastic cancer, hepatocellular carcinoma, lung adenocarcinoma/ non-small cell carcinoma, osteosarcoma, colon cancer and ovarian carcinoma (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)31).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that abnormal expression of mi-croRNAs can regulate some pivotal biological behaviors, including chemotherapy resistance, which promoted chemotherapy failure and caused a poor prognosis [19][20][21][22][23][24][25]. This study firstly found that miR-130b was highly expressed in doxorubicin-insensitive BUC tissues and cell lines, which indicated that the aberrant expression of miR-130b was involved in chemotherapy resistance of BUC and its up-expression was negatively related to doxorubicin sensitivity in BUC.…”
Section: Discussionmentioning
confidence: 72%
“…Huang et al [21] found that inhibition of autophagic flux to enhance the efficiency of GEM in GEM-resistant BC cells. In addition, we have identified many studies reporting that the mechanism of action for mitigating GEM resistance is associated with autophagy [22,23] . Interestingly, it was reported that a novel protein phosphatase, Completer's Transactivated Protein 1 (CSTP1), interacts with and specifically dephosphorylates Akt at Ser473 in vivo and in vitro to arrest cell cycle progression and promote apoptosis, and that the Ser473 site of Akt is a major cellular target of CSTP1, the expression of which is selectively down-regulated in non-invasive BC tissues [24] .…”
Section: Resultsmentioning
confidence: 99%